Ethyl acetate extract of Ruta graveolens: a specific and potent inhibitor against the drug-resistant EGFR_T790M mutant in NSCLC - Kumar, Vikas; Chauhan, Leena; Singh, Deepa; Kumar, Akash; Kulandaisamy, Rajkumar; Kushwaha, Tushar; Baswal, Kamal; Singh, Rajan; Kumar, Saroj; Gholap, Shivajirao L.; Hariprasad, P.; Dadinaboyina, S. Babu; et al. (Frontiers in Pharmacology, 2025)
Lung cancer, the second leading cause of cancer mortality, requires the development of novel therapeutic strategies due to emerging drug resistance and toxicity. With this objective, the present work explored the therapeutic potential of R. graveolens leaf extracts against EGFR_T790M-mediated drug resistance in NSCLC. To this end, we evaluated the functional and therapeutic potential of a panel of polar and non-polar solvent extracts using various in vitro assay systems. Among the extracts tested, EAE exhibited superior kinase inhibitory activity, which was more pronounced against the EGFR_T790M mutant phenotype. Accordingly, EAE exhibited a favorable cytotoxicity profile and potent growth inhibition of EGFR_T790M-positive NSCLC cells, as evident from its superior IC50 values in this cell type. Flow cytometry analysis further validated its inhibitory effects on the cell cycle and, well-supported by the data from the TUNEL assay, suggested induction of apoptosis in EAE-treated cells in a dose-dependent manner. Finally, mechanistic studies in EAE-treated cells showed that these outcomes were due to concentration-dependent inhibition of EGFR phosphorylation at Tyr1068 and Tyr1173. Importantly, this inhibition was consistently more pronounced in H1975 cells expressing the EGFR_T790M mutant phenotype. Further, pull-down assays, followed by mass spectrometry analysis, identified the most promising molecules within EAE. Together, the study highlighted the therapeutic potential of EAE from the leaves of Ruta graveolens for treating EGFR_T790M-mediated drug resistance in lung cancer.